Tahlilan Tradition as Media for National Character Education - Alif Nurul Mubarok (Lakpesdam PCNU Kota Salatiga, 2021)
Tahlilan is one of the ancestral traditions of the Indonesian nation which is rich in social values. Apart from functioning as a religious ritual, it is also meaningful as a medium for character education. Through the field research method, this research seeks to reveal the values of character education contained in the tahlilan tradition, especially tahlilan carried out by the people of Losari Village, Losari District, Cirebon Regency. The results of this study found that there are so many values of character education contained in the tahlilan tradition in Losari Village, namely; diversity, social concern, hard work, and discipline. Thus, it can be said that the tahlilan tradition can function as the basis for character education for the Indonesian nation, especially among the Indonesian Muslim community.